Battleground : the family - Brackett, Kimberly P. (Greenwood Press, 2009)
Everyone is part of a family, but what constitutes a family is one of the most hotly debated issues in the United States today. Battleground: The Family provides extensive coverage of those critical issues in U.S. culture concerning current and future family life, such as dating, marriage, parenting, work and family, abuse, and divorce. The scholarly contributors to this set provide unbiased coverage on these often incendiary topics, allowing students to assess the role of these controversies in their own lives. Entries thoroughly introduce the topic of concern, describe the problem as it currently exists, provide context for the controversies surrounding it, synthesize the current knowledge on the topic, and guide the reader to additional areas for consideration. Battleground: The Family serves as a starting point for those advanced high school and beginning undergraduate students who wish to pursue a more detailed study of family controversies and cultural concerns for classroom assignments. Non-specialist readers will also find this a useful resource in critically assessing current trends and conflicts in constituent groups' conceptions of family. - Publisher.